The HPV vaccine: knowledge and attitudes among public health nurses and general practitioners in Northern Norway after introduction of the vaccine in the school-based vaccination programme - Karin Nilsen; Olaf Gjerløw Aasland; Elise Klouman (Taylor & Francis Group, 2017)
Objective: To investigate knowledge of and attitudes to human papillomavirus (HPV) infection, HPV vaccination, cervical cancer, related sources of information and factors associated with willingness to vaccinate one's own daughter among primary health care (PHC) personnel. Design: Cross-sectional study. Setting: PHC. Subjects: All public health nurses (PHNs) and general practitioners (GPs) in Northern Norway were invited to answer a structured electronic questionnaire; 31% participated (N = 220). Main outcome measures: Self-reported and actual knowledge, information sources, attitudes and willingness to vaccinate their (tentative) daughter. Results: 47% of respondents knew that HPV infection is a necessary cause of cervical cancer. PHNs had higher self-reported and actual knowledge about HPV vaccination and cervical cancer than GPs. PHNs used the Norwegian Institute of Public Health's numerous information sources on HPV, while GPs had a low user rate. 88% of PHNs and 50% of GPs acquired information from the pharmaceutical industry. 93% PHNs and 68% of GPs would vaccinate their 12-year-old daughter. In a multivariate logistic regression analysis, willingness to vaccinate one's daughter was positively associated with younger age, being PHN (OR = 5.26, 95%CI 1.74-15.94), little concern about vaccine side effects (OR = 3.61, 95%CI 1.10-11.81) and disagreement among experts (OR = 7.31, 95%CI 2.73-19.60). Conclusions: Increased knowledge about HPV infection and vaccination is needed, particularly among GPs. Those least concerned about side effects and disagreements among experts were most likely to vaccinate their daughter. These findings are of interest for public health authorities responsible for the Norwegian vaccination and cervix cancer screening programmes, and providers of training of PHC personnel.Key points One year after introduction of HPV vaccination among 12-year-old schoolgirls in Norway, a cross-sectional study in Northern Norway among general practitioners (GPs) and public health nurses (PHNs) showed that • barely half of PHC professionals knew the causal relationship between HPV infection and cervical cancer • PHNs and GPs had higher self-reported than actual knowledge about HPV vaccination and cervical cancer nearly all PHNs and two thirds of GPs wanted to vaccinate their 12-year-old daughter. Those most concerned about side effects and disagreement among experts were less likely to vaccinate.